Foliar Application of Copper Oxide Nanoparticles Increases the Photosynthetic Efficiency and Antioxidant Activity in Brassica juncea. (27th March 2022) - Faraz, Ahmad; Faizan, Mohammad; Hayat, Shamsul; Alam, Pravej
Abstract : In the last few decades, use of copper oxide nanoparticles (CuO NPs) has been increased significantly that eventually included as a growth stimulator. This makes it essential to examine their impact on several plants. In the study detailed here, we investigated the effects of CuO NPs on the growth, physiological efficiency, biochemical assays, and antioxidant system in the mustard plant. Varying concentrations (0, 2, 4, 8, and 16 mg/L) of CuO NPs were applied at 25 days after sowing (DAS), and sampling took place at 30 and 45 DAS. The results indicate that CuO NPs-treated plants registered an increase in the growth and biomass over their respective control. Among different concentrations of CuO NPs (0, 2, 4, 8, and 16 mg/L), 8 mg/L proved to be the optimum foliar spray treatment and increase the chlorophyll content, net photosynthetic rate, leaf proline content, and antioxidant enzymes activity. We concluded that CuO NPs interact with meristematic cells triggering biochemical pathways conductive to an enhancement of the growth attributes. Further studies are needed to investigate the mechanisms of CuO NPs in mustard.